The Protective Effect of DiDang Tang Against AlCl3-Induced Oxidative Stress and Apoptosis in PC12 Cells Through the Activation of SIRT1-Mediated Akt/Nrf2/HO-1 Pathway - Lu, Jing; Huang, Qingxia; Zhang, Dongmei; Lan, Tianye; Zhang, Ying; Tang, Xiaolei; Xu, Peng; Zhao, Dexi; Cong, Deyu; Zhao, Daqing; Sun, Liwei; Li, Xiangyan; et al. (Frontiers in Pharmacology, 2020)
Abstract： Aluminum (Al) is considered a pathological factor for various neurological and neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson’s disease (PD). The neurotoxicity of aluminum can cause oxidative brain damage, trigger apoptosis, and ultimately cause irreversible damage to neurons. DiDang Tang (DDT), a classic formula within traditional Chinese medicine for promoting blood circulation and removing blood stasis and collaterals, is widely used for the treatment of stroke and AD. In this study, models of oxidative stress and apoptosis were established using AlCl3, and the effects of DDT were evaluated. We found that DDT treatment for 48 h significantly increased cell viability and reduced the release of lactate dehydrogenase (LDH) in AlCl3-induced PC12 cells. Moreover, DDT attenuated AlCl3-induced oxidative stress damage by increasing antioxidant activities and apoptosis through mitochondrial apoptotic pathways. Additionally, DDT treatment significantly activated the Sirtuin 1 (SIRT1) -mediated Akt / nuclear factor E2 related factor 2 (Nrf2) / heme oxygenase-1 (HO-1) pathways to limit AlCl3-mediated neurotoxicity. Our data indicated that DDT potently inhibited AlCl3-induced oxidative-stress damage and apoptosis in neural cells by activating the SIRT1-mediated Akt/Nrf2/HO-1 pathway, which provides further support for the beneficial effects of DDT on Al-induced neurotoxicity.